2003
DOI: 10.1016/s0895-4356(03)00208-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of COPD on health-related quality of life independent of the influence of comorbidity

Abstract: COPD patients can be impaired in all domains of HRQL. However, impairments in physical functioning, vitality, and general health are related to COPD and to some extent to comorbidity, while impairments in social and emotional functioning do not seem to be related to COPD, but only to comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
69
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 23 publications
9
69
1
6
Order By: Relevance
“…The SF-36 physical and mental component scores for patients with LAM are worse than those for the general U.S. healthy population with no chronic conditions (55.3 and 53.4, respectively) but better than those for patients with COPD seen in one study with a mean FEV 1 of 45% predicted (35.9 and 47.7, respectively) (26,39). Interestingly, the lack of physiologic correlation with the SF-36 mental component, which is similar to patients with COPD (38,40), suggests both groups develop coping mechanisms or have good support systems.…”
Section: Discussionmentioning
confidence: 90%
“…The SF-36 physical and mental component scores for patients with LAM are worse than those for the general U.S. healthy population with no chronic conditions (55.3 and 53.4, respectively) but better than those for patients with COPD seen in one study with a mean FEV 1 of 45% predicted (35.9 and 47.7, respectively) (26,39). Interestingly, the lack of physiologic correlation with the SF-36 mental component, which is similar to patients with COPD (38,40), suggests both groups develop coping mechanisms or have good support systems.…”
Section: Discussionmentioning
confidence: 90%
“…Concurring with our findings, Wijnhoven et al [4] reported that comorbid diseases significantly contributed to all domains of HRQOL in patients with COPD. Van Manen et al [26] suggested that impairment in social and emotional functioning in patients with COPD did not seem to be related to COPD, only to comorbid pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…COPD patients suffer from a high proportion of comorbid conditions [8][9][10][11] and up to two-thirds of individuals suffering from COPD die of non-pulmonary causes [12,13]. Comorbidities also influence important patient-centred outcomes, such as health status [14,15], response to therapeutic intervention [16], and frequent hospital readmissions [17,18]. The majority of studies of COPD comorbidities report the relationship between a single or small number of comorbidities [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%